2019
DOI: 10.21276/ijcmr.2019.6.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis: Clinical Spectrum, Bacteriological Profile and Antibiotic Sensitivity Patterns in Neonatal Intensive Care Unit in a Tertiary Care Hospital

Abstract: Introduction: Neonatologists face a perpetual challenge in managing neonatal septicaemia due to changing patterns of the microbial flora and their antibiotic sensitivity. The present study was designed to evaluate the clinical spectrum, bacteriological profile, antibiotic sensitivity patterns in neonates with suspected septicaemia in a tertiary care teaching hospital. Material and Methods: This prospective observational study was carried out in neonatal intensive care unit for a period of nine months. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 8 publications
11
6
0
Order By: Relevance
“…Respiratory distress syndrome was the major clinical features amongst other features with 36.0% in this study which is similar to recent studies by Kurma et al [30] with 31.2%, Khante et al [37] with 34.15% and 56% for study by Sathyamurthi et al [38]. This indicates that, this clinical feature has been one of the greatest problems to neonates till date.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Respiratory distress syndrome was the major clinical features amongst other features with 36.0% in this study which is similar to recent studies by Kurma et al [30] with 31.2%, Khante et al [37] with 34.15% and 56% for study by Sathyamurthi et al [38]. This indicates that, this clinical feature has been one of the greatest problems to neonates till date.…”
Section: Discussionsupporting
confidence: 90%
“…This study has demonstrated the continued role of septicemia in pediatric morbidity and mortality in this environment. In this study, it was observed that early-onset neonatal septicemia was more common than late-onset neonatal septicemia, this is similar to reports of Chako and Sohi in [26], Rasul et al [27], West and Tabansi in [28], Peterside et al [29], and Kurma, et al [30] in which early-onset septicemia generally was more common.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations